Comparative analysis of survival rates of pre- and postmenopausal patients with early breast cancer - N. B. Bekkeldieva; V. F. Semiglazov; P. V. Krivorotko; V. V. Mortada; A. V. Komyahov; K. Yu. Zernov; S. S. Yereshchenko; T. T. Tabagua; R. S. Pesotskiy; K. S. Nikolaev; Ya. I. Bondarchuk; N. S. Amirov; et al. (Опухоли женской репродуктивной системы)
Introduction. Breast cancer, which occurs in young women, is more often classified as a biologically aggressive subtype (HER2+ and triple negative) compared with postmenopausal patients. At the same time, it is important to know whether age, in itself, determines a less favorable outcome of the disease in young patients.Aim. To evaluate overall and recurrence-free survival rates in premenopausal and postmenopausal patients who underwent various levels of surgery and received neoadjuvant and adjuvant systemic therapy.Materials and methods. Of the 3,450 analyzed patients, the final analysis included 265 patients with breast cancer (clinical stage T1–3N0–1M0) who received treatment between 2011 and 2019, who were divided into 2 groups depending on age category, biological tumor subtype, types of neoadjuvant and adjuvant treatment.Results. Of 265 included patients, 162 (61.1 %) were premenopausal women, 103 (38.9 %) were postmenopausal women. The median follow-up was 5 years. The 5-year overall survival was 96.8 % (95 % confidence interval (CI) 92.6–98.7) in premenopausal patients and 95.1 % (95 % CI 88.5–97.9) in postmenopausal patients. The differences in overall survival estimated using the likelihood ratio test were not statistically significant (p = 0.927). The 5-year recurrencefree survival rate was 77.6 % (95 % CI 70.3–83.3) in premenopausal patients and 84.2 % (95 % CI 75.6–90.0) in postmenopausal patients. The differences in disease-free survival estimated using the likelihood ratio test were not statistically significant (p = 0.253).Conclusion. When comparing patients with early breast cancer, overall and relapse-free survival did not depend on menopausal status. It is necessary to conduct randomized trials to determine the effectiveness of drug therapy.